2011
DOI: 10.1111/j.1750-3841.2011.02263.x
|View full text |Cite
|
Sign up to set email alerts
|

Anthocyanins Remain Stable during Commercial Blackcurrant Juice Processing

Abstract: This article provides crucial data directly applicable to commercial juice processing, such as improving anthocyanin yield and practical considerations for anthocyanin stability and degradation. This aspect is particularly pertinent considering the current commercial interest in anthocyanin-derived phenolic acids and their health-related benefits. Further research and development targets in the area of commercial juice product development are identified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 15 publications
0
12
0
Order By: Relevance
“…As pectinolytic enzymes were used to produce this juice the lower antioxidant activity may be an effect of the enzyme treatment. On the other hand, an enzyme treatment produced no reduction in the anthocyanins content of blackcurrant juice as compared to the berries [21].…”
Section: Processing Effects On Polyphenolsmentioning
confidence: 78%
“…As pectinolytic enzymes were used to produce this juice the lower antioxidant activity may be an effect of the enzyme treatment. On the other hand, an enzyme treatment produced no reduction in the anthocyanins content of blackcurrant juice as compared to the berries [21].…”
Section: Processing Effects On Polyphenolsmentioning
confidence: 78%
“…A more gradual and sustained insulinaemic response could potentially increase satiety during intermeal intervals (4) and a lowered postprandial glycaemia is likely to protect the optimum functionality of pancreatic β cells, the vascular endothelium and hepatic lipid metabolism. However, there may be significant technical challenges for the food and drink industry in formulating products with the desired characteristics in terms of physical and chemical stability (114) , bioavailability (107) and palatability (115) . Anthocyanin contents vary among species and cultivars, and are subject to genetic, agricultural and environmental factors as well as storage and processing conditions (116)(117)(118) .…”
Section: Discussionmentioning
confidence: 99%
“…In general, freezing causes moderate variations in phenolic compounds; a study on four raspberry cultivars showed variable results, ranging from no change to an increase of 12% and decreases of 21% and 28%, during 12 months frozen storage . No loss of anthocyanins was observed after pasteurization, decantation, filtration and concentration of blackcurrant juice . On the other hand, thermal pasteurization and high‐pressure processing caused significant change in strawberry fruit antioxidant capacity .…”
Section: Factors Affecting Antioxidants In Berriesmentioning
confidence: 99%